A cross-national perspective on school bullying in Northern Ireland: A supplement to Smith, et al. - MC GUCKIN, CONOR (My University, 2003)
There is great value in exploring the prevalence of school bullying from a cross-national perspective. Smith, Morita, Junger-Tas, Olweus, Catalano, and Slee (1999) presented a cross-national perspective on the nature, prevalence, and correlates of school bullying that encompassed a wide range of countries. However, Northern Ireland was not included, despite it potentially being an important country to include; given its volatile, social, ethnic, and religious history ? leading to the concern that the population has become somewhat habituated to low level aggression. Thus, the present paper provides a review of the current literature on school bullying in the Northern Ireland school system. Evidence presented suggests that the incidence of school bullying in Northern Ireland may be higher than those found in the rest of Ireland and the United Kingdom.
PUBLISHED
Keywords: Bullying